A Study on Performance and Progress of Indian Banking Sector: A Comparative Analysis of Bank Performance in the Indian Banking Sector (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Financial sector plays a pivotal role in the economic development. It is generally agreed that a strong and healthy banking system is a prerequisite for sustainable economic growth. Banks in India have been undergoing major challenges in the dynamic environment over the past few years as it is evident from several parameters, including No. of offices, No. of employees, Business per employee, Profit per employee, Net Worth, Deposits, Investments, Advances, Interest income, Other income, Interest expended, Operating expenses, Cost of Funds (CoF), Return on advances adjusted to CoF, Wages as to total expenses, Return on Assets, CRAR and Net NPA ratio In order to resist negative shocks and maintain financial stability, it is important to identify theprofile of the banks. The current study is mainly concerned with the analysis of comparative profiles of Public Banks, Private Banks and Foreign Banks in India during the period of 2006-13 that reflects the impact of new competitive environment on the bank’s performance in terms of various selected parameters. The Data was collected through secondary sources from Trend and Progress Report of RBI and the tool used for data analysis of the profile of bank group wise is Compound Annual Growth Rate (CAGR) which is expressed in percentages. The results have found strong evidence that the Private Sector Banks surpasses the other bank groups and topped the position in all the parameters, while Public Sector Banks and Foreign Banks are just competing for the 2nd and the 3rd position.